Terahertz Wave Detection and Imaging with a Hot Rydberg Vapour - Wade, Christopher G. (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This book details groundbreaking experiments for the sensing and imaging of terahertz-frequency electromagnetic radiation (THz) using Rydberg atoms. The major advances described include the development and implementation of a new technique for THz imaging using atomic fluorescence; the demonstration of a THz-driven phase transition in room-temperature atomic vapour; and a novel method for probing the excited-state dynamics of atoms using quantum beats. The work has formed the basis for several articles published in journals including Nature Photonics and the Physical Review, and has sparked industry interest, becoming the subject of ongoing collaborative research and development. This exceptionally well-written book provides a definitive account of terahertz sensing with Rydberg atoms.